A CONCEPTUAL FRAMEWORK FOR SOFTWARE REQUIREMENTS VALIDATION - Ahmed , Ahmed A.; Ayman E. Khedr; Sherif A. Kholeif (IJRDO-Journal of Applied Science, 2019)
Requirements validation is one of the most significant and critical parts of the requirements engineering. This activity ensures that the set of requirements is accurate, right, complete, and consistent. Requirements validation is considered as the key activity because mistakes found in a software requirements document can lead to extensive rework costs when they are discovered either during development or after the system is in service. There are some commonly used bases to validate user requirements such as: Natural language, Design description languages, Graphical notations and Mathematical specification languages. Whereas the graphical notations are the most suitable means to be used in software requirements validation because it is easy to understand, and it can be easily created by analyst and time took. Therefore, this paper adopts the map concept which is a graphical technique for discovering the hidden flaws in software requirements in the early phases of software development lifecycle.